A regard over the other - Beigel, Fernanda (FCL-UNESP Laboratório Editorial, 2007)
Among the many goals of this paper, the main one was to say that there is really a bond between the ideas of Mariátegui and Gramsci, so far exaggerated. In order to do it, there is exposition of the simple distinction (absolutely obvious in the gramscian studies but not so evident among the mariateguians) between the views of thought and action, intimately connected but so different in practice: the Gramsci´s ordinovistic experience and conception of the world.